2021
DOI: 10.1051/meca/2020101
|View full text |Cite
|
Sign up to set email alerts
|

A study on the high-efficiency mixer of the SCR system

Abstract: A new mixer for a diesel engine after-treatment system is developed to meet the requirements of China VI emission regulation. As for the structure of the mixer, it is surrounded by spiral blades, and the center is staggered with small blades, which is conducive to the crushing of urea droplets and can make the droplets fully mixed with air, improve the conversion efficiency of nitrogen oxides (NOx) and reduce ammonia leakage. The numerical analysis, engine bench test, and vehicle road test were carried out on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…[24] In addition, the NOx conversion effectiveness will be increased, and the ammonia slip, which is also an emission, will be reduced. [25] [26] UI can be used to evaluate variables other than velocity. For example, Capetillo et…”
Section: Resultsmentioning
confidence: 99%
“…[24] In addition, the NOx conversion effectiveness will be increased, and the ammonia slip, which is also an emission, will be reduced. [25] [26] UI can be used to evaluate variables other than velocity. For example, Capetillo et…”
Section: Resultsmentioning
confidence: 99%
“…It was mentioned in [13] that values over 0.94 [−] are considered as good results, but some authors aim at even higher numbers such as 0.98 [−]. [17] In this study most of the variants meet the lower requirement in order to not disqualify too many variants. Therefore it is necessary to use a higher value, closer to that recommended by Lu et al in their study, so 0.97 is chosen.…”
Section: Fig 3 Illustration Of the Injection Direction Logic 3 Evalua...mentioning
confidence: 94%
“…Flow maldistribution at the catalyst's front face causes bigger ageing effects in these zones, resulting in worse overall species conversion efficiency. Lu, et al [17] proposed a new mixer design for diesel engines. It was observed that by employing this mixer, urea droplets fully mixed with flue gas and increased NOX conversion efficiency, with velocity uniformity index and ammonia uniformity index of 0.98 and 0.95, respectively.…”
Section: Review Of Recent Workmentioning
confidence: 99%